PREDIKSI PRODUKSI ROTI COKLAT BERDASARKAN DATA TRENDS GOOGLE MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING - Asrianto, Rudy; Yanna Anggraini (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2021)
To win the competition in the market, it requires the ability of a professional company manager to be able to meet market demand in an appropriate amount by paying attention to the inventory of goods so that they can get maximum profit. But the production process that occurs at Rotte Bakery is erratic every day which only relies on demand estimates, causing shortages and advantages in each production. Therefore, predictions are needed to make the right decisions in predicting the amount of production that will be produced in the following year. The data used are historical data on brown bread sales at Rotte Bakery for the period 2018-2020 and search data for brown bread in Riau for the period 2018-2020 (Google Trend). The results obtained from this study are the results of the analysis of the exponential method to obtain predictive information and the level of accuracy with MAPE to find the smallest error